TFP convergence in German states since reunification: Evidence and explanations - Michael C. Burda; Battista Severgnini (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
A quarter-century after reunification, labor productivity in eastern Germany continues to lag systematically behind the West. Denison-Hall-Jones point-in-time estimates point to large gaps in total factor productivity as the proximate cause, and auxiliary measurements which do not rely on capital stock data confirm a slowdown in TFP growth after 2000. Strikingly, capital intensity in eastern Germany, especially in industry, has overshot values in the West, casting doubt on the embodied technology hypothesis. Indeed, TFP growth is negatively associated with rates of expenditures on both total investment and plant and equipment. The best candidates for explaining the stubborn East-West TFP gap are the low concentration of managers in the East and the insufficient R&D expenditure, rather than the concentration of firm headquarters and R&D personnel.
Keywords: D24; E01; E22; O33; O47; 330; productivity; regional convergence; German reunification